Pemberdayaan Masyarakat dalam Pelestraian Hutan dan Pertanian Berkelanjutan di Sekitar Suaka Margasatwa Karakelang, Sulawesi Utara - Widyanto, Adi; Mulatsih, Sri; Karlinasari, Lina (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
The protection of Karakelang wildlife sanctuary has been challenged by forest encroachment, timber harvesting and wildlife poaching - all of which are attributed to social economic condition of the communities living in the vicinity. A community based conservation program was delivered to strengthen communities’ role in maintaining forest integrity while making good income from sustainable agriculture. This action research using mixed methodology evaluates the influence of program delivery in changing the knowledge, attitude and practice of forest protection and sustainable agriculture among beneficiaries in three villages. Data was collected using structured interview, while other supporting information was taken from project reports and field notes. The Wilcoxon Signed Rank Test reveals that program has influence in changing the knowledge of respondents in both forest protection and sustainable agriculture, as well as in the change of attitude and practice regarding sustainable agriculture. However, it does not have influence in changing their attitude and practice toward forest protection. As shwon by economic indicator, program has contributed in providing new source of income to farmers household. The result of logistic regression shows that age, education, land ownership and income has influence in the change of people’s knowledge about forest biodiversity. Only age has influence in change of attitude towards sustainable agriculture, and only land ownership has influence on support to forest protection.